Trabalho pedagógico em um Núcleo de Educação Popular: possibilidade de Práxis Pedagógica? - Schio, Leticia Genro (2019)
This work investigated how the theory of the permanent revolution underlies, theoretically and politically, the pedagogical work developed by the educators of the "13 de Maio Núcleo de Educação Popular", especially what is done in the course "How Society Works I". To this end, it was a bibliographic research, and a study of didatic materials produced by the educators of the referred popular education entity and a questionnaire answered by an educator was carried out. Studies were conducted about the historicity of the theory of permanent revolution elaborated by Marx and Engels in 1850; about the historical constitution of the 13 de Maio NEP in relation to the intrinsic relationship of the class struggle movement in Brazil during the Business-Military Dictatorship (1964 - 1985), in the period of redemocratization of the country, until the present day;the study of productions about pedagogical work (especially those produced by Kairós - Research and Studies Group on Work, Education and Public Policy); and also, the study of the script of the course “How Society Works I” in the light of the elements of the theory of permanent revolution and how these elements are expressed in the pedagogical work done by the educators in the course. The choice for this specific course was understood because it expresses, in a synthetic form, elements that in the set of courses held by 13 de Maio are seen in more depth and also because this is the course most widely known by set of the Brazilian working class. The understanding that the pedagogical work carried out in the context of theoretical-political formation assumes specific characteristics that differ from the particularities of that performed in formal school institutions, it led the investigation about these characteristics. The considerations reached express that this is a pedagogical work intrinsically linked to the interests of the working class, this is a pedagogical work based on the rigorous knowledge about what is the capital and how this social relationship of control and exploitation of work is established and is reproduced from its innumerable constituent and contradictory mediations.